The Effectiveness of International Financial Reporting Standards in Minimizing Information Asymmetry - CHALA, Tetyana; HRABYNSKA, Iryna; PTASHCHЕNKO, Olеna; PERCHUK, Oksana; POSADNIEVA, Oksana; BIOKO, Olga (Theoretical and Practical Research in Economic Fields, 2024)
Information asymmetry is an important problem of financial markets, which creates unequal conditions for different investors. The aim of the research is to analyse the impact of the implementation of International Financial Reporting Standards (IFRS) on the change in the relationship between a number of financial indicators and the company’s market value. The latter was taken as an indicator of information asymmetry arising from investors’ speculative expectations. The research employs methods of correlation, regression, and comparative analysis. The study established an increase in the correlation between Price-to-Earnings (P/E) ratio and market capitalization (Market cap) for a sample of Saudi Arabian companies after the IFRS implementation. However, the previously obtained conclusions were not confirmed after checking the results with the data of each individual company. Moreover, it was found that for most companies the correlation between P/E ratio and Market cap significantly weakened after the IFRS implementation. It can be assumed that before the mandatory IFRS implementation, the increase in Market cap could occur mainly on the basis of investors’ expectations. However, expectations could not be met because of a significant level of information asymmetry. Therefore, the decrease in correlations between P/E ratio and Market cap may indicate a more critical assessment of companies by investors due to increased transparency of financial information. Further research may focus on the analysis of other factors influencing the level of information asymmetry, such as improving the quality of integrated reporting and corporate governance.